The importance of deposit insurance credibility - Bonfim, Diana (2023)
Funding Information: The authors thank Rui Albuquerque, Piergiorgio Alessandri, Franklin Allen, Carlo Altavilla, Nuno Alves, Thorsten Beck (editor), Andrada Bilan, Martin Brown, Olivier De Jonghe, Robert DeYoung, Erietta Exchar- chopoulou, João Freitas, Itay Goldstein, Claudia Girardone, Isaac Hacamo, Balint Horvath, Harry Huizinga, Artashes Karapetyan, Catherine Casanova, Slawek Kozdras, Luc Laeven, Martien Lamers, Agnese Leonello, Steven Ongena, Teodora Paligorova, Ettore Panetti, Diane Pierret, Jean Charles Rochet, Enrico Sette, André Silva, Helmut Stix, Raluca Roman, Javier Suarez, Razvan Vlahu, Ansgar Walther, two anonymous referees, and participants at the DNB/EBC/CEPR Conference on Avoiding and Resolving Banking Crises, 2017 EEA, 3rd IWH-FIN-FIRE Workshop on Challenges to Financial Stability, 2018 ASSA/IBEFA, 2018 CEBRA Annual Meeting, 2018 EBA Policy Research Workshop, SAFE Annual Conference on Sustainable Architecture for Finance – Where Are We Now and Where Are We Going, 2019 Biennial IADI Research Conference, SRB–FBF–SAFE conference on Bank Crisis Management – What next?, and in seminars at Banco de Portugal, University of Zurich, and University of Groningen for insightful comments. Nuno Silva offered invaluable assistance in the early stages of this project. Bonfim acknowledges grants UID/GES/00,407/2020 and PTDC/EGE-OGE/6041/2020 from the Portuguese Foundation for Science and Technology-FCT. The views stated herein are those of the authors and are not necessarily the views of Banco de Portugal, the European Central Bank, the Eurosystem, the Federal Reserve Bank of New York or the Federal Reserve System. Funding Information: The authors thank Rui Albuquerque, Piergiorgio Alessandri, Franklin Allen, Carlo Altavilla, Nuno Alves, Thorsten Beck (editor), Andrada Bilan, Martin Brown, Olivier De Jonghe, Robert DeYoung, Erietta Exchar- chopoulou, João Freitas, Itay Goldstein, Claudia Girardone, Isaac Hacamo, Balint Horvath, Harry Huizinga, Artashes Karapetyan, Catherine Casanova, Slawek Kozdras, Luc Laeven, Martien Lamers, Agnese Leonello, Steven Ongena, Teodora Paligorova, Ettore Panetti, Diane Pierret, Jean Charles Rochet, Enrico Sette, André Silva, Helmut Stix, Raluca Roman, Javier Suarez, Razvan Vlahu, Ansgar Walther, two anonymous referees, and participants at the DNB/EBC/CEPR Conference on Avoiding and Resolving Banking Crises, 2017 EEA, 3rd IWH-FIN-FIRE Workshop on Challenges to Financial Stability, 2018 ASSA/IBEFA, 2018 CEBRA Annual Meeting, 2018 EBA Policy Research Workshop, SAFE Annual Conference on Sustainable Architecture for Finance – Where Are We Now and Where Are We Going, 2019 Biennial IADI Research Conference, SRB–FBF–SAFE conference on Bank Crisis Management – What next?, and in seminars at Banco de Portugal, University of Zurich, and University of Groningen for insightful comments. Nuno Silva offered invaluable assistance in the early stages of this project. Bonfim acknowledges grants UID/GES/00,407/2020 and PTDC/EGE-OGE/6041/2020 from the Portuguese Foundation for Science and Technology-FCT. The views stated herein are those of the authors and are not necessarily the views of Banco de Portugal, the European Central Bank, the Eurosystem, the Federal Reserve Bank of New York or the Federal Reserve System. Publisher Copyright: © 2023